Penerapan Algoritma Knuth-Morris-Pratt Dalam Sistem Jasa Konsultan berbasis Mobile dan Web - Kristian Telaumbanua; Florida N Damanik; Mirza Ilhami; Erlanie Sufarnap (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
With the increasing of human life aspects, various applications for online consulting service providers have emerged with different fields and backgrounds. To assist the process of selecting consultants according to the preferences of certain users, a consultant search system that covers several consulting areas at once is implemented, which aims to make it easier for users to find consultants that suit their needs. Knuth-Morris-Pratt is a string matching algorithm whose search is based on text and patterns, KMP is used to find where a pattern is found in a collection of other strings with a larger size, this algorithm is also include as one of the fastest and has a small complexity. In this final project, an overview of the application and feature testing using black-box testing will be presented, along with a comparison of the Knuth-Morris-Pratt search algorithm with other search algorithms. The system development methodology used is the waterfall methodology. The results of this final project can be concluded that the application of the Knuth-Morris-Pratt algorithm on mobile and web-based consulting services search applications can assist clients in providing better and more efficient searches.